1977
DOI: 10.1002/1097-0142(197705)39:5<1940::aid-cncr2820390505>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Dose response evaluation of adriamycin in human neoplasia

Abstract: Because patients treated with 60-90 mg/m2 every three to four weeks reach cardiotoxic doses of 550 mg/m2 within 36 weeks, prolonged treatment with Adriamycin is limited. The purpose of this study was to determine whether lower doses could be given over longer periods without loss of efficacy. Good risk patients treated with 75,60, or 45 mg/m2 had remission rates of 25,27, and 19%; poor risk patients treated with 50 and 25 mg/m2 had remission rates of 16 and 12% respectively. Although a dose response was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
78
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(83 citation statements)
references
References 11 publications
3
78
0
Order By: Relevance
“…Comparison between mdrl and gst-7 mRNA levels in all the breast samples assayed shows a low level of correlation which is only slightly significant (r = 0.48, P <0.1). Thus for some of these tumours coexpression of Discussion Doxorubicin is widely used in the treatment of advanced breast cancer, with an overall response rate among breat cancer patients of about 55% (Blum & Carter, 1974;O'Bryan et al, 1977). This means that almost half the patients are resistant to doxorubicin from the outset of treatment.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Comparison between mdrl and gst-7 mRNA levels in all the breast samples assayed shows a low level of correlation which is only slightly significant (r = 0.48, P <0.1). Thus for some of these tumours coexpression of Discussion Doxorubicin is widely used in the treatment of advanced breast cancer, with an overall response rate among breat cancer patients of about 55% (Blum & Carter, 1974;O'Bryan et al, 1977). This means that almost half the patients are resistant to doxorubicin from the outset of treatment.…”
Section: Methodsmentioning
confidence: 94%
“…However, both inherent and acquired resistance are in many cases major obstacles in successful treatment (O'Bryan et al, 1977). Increased levels of expression of the mdrl gene, which codes for a 175 kDa plasma membrane associated glycoprotein, and the gst-rc gene, encoding the anionic isozyme of glutathione Stransferase (GSTh) have previously been shown in doxorubicin (adriamycin) resistant cell lines, derived by drug selection in culture Riordan et al, 1985;Scotto et al, 1986;Cowan et al, 1986;Deffie et al, 1988;Van der Bliek et al, 1988).…”
mentioning
confidence: 99%
“…Doxorubicin and ifosfamide are considered the cornerstones of treatment for advanced STS, consistently producing responses as monotherapy in more than 20% of previously untreated patients (Pinedo and Kenis, 1977). Most studies have demonstrated a clear doseresponse relationship for both of these drugs (O'Bryan et al, 1977, Antman et al, 1990. Combinations of the active drugs have shown improved response rates, but are often limited by increased toxicity (Benjamin, 1987).…”
mentioning
confidence: 99%
“…6,7 There is strong evidence for a dose-response relationship for doxorubicin and ifosfamide. 8,9 For optimal response rates it seems essential to achieve a dose intensity of greater than 65 mg/m 2 for doxorubicin and greater than 5 g/m 2 for ifosfamide. 10,11 In the last decade, hematopoietic growth factors such as granulocyte colony-stimulating factor (G-CSF) and granulocyte-macrophage colony-stimulating factor (GM-CSF) have entered clinical trials in an attempt to administer escalated-dose chemotherapy regimens without inducing fatal neutropenia.…”
mentioning
confidence: 99%